Complete Blood Count parameters could predict malignancy in breast lesions - Ozer, Bahri; Catal, Oguz; Peltek Ozer, Songul; Keyif, Fatih; Sit, Mustafa; Kama, Nuri (Annals of Medical Research, 2021)
Aim: Inflammatory response plays an important role in the development and progression of various cancers, including breast cancer. The aim of present study is determining Complete Blood Count parameters as possible predictors of malignancy in breast lesions. Material and Methods: Patients with BI-RADS-4 breast disease were studied between 2010 and 2017 retrospectively. Patients with lesions detected radiologically were included in the study. According to the histopathological results, the study cohort was divided into two groups, either benign or malignant. Final blood counts of the patients before pre-biopsy were evaluated in preoperative peripheral blood measurements. When blood was taken, care was taken not to have other causes of leukocytosis in the patient. Complete Blood Count parameters were compared in these groups. Results: A total of 331 women with BI-RADS 4 lesions enrolled to the study. Mortality and morbidity were not observed after breast biopsy in patients. Platelet (p=0.04), platelet to lymphocyte ratio (p=0.006) and red cell distribution width to platelet ratio (p=0.032) values of the patients with BI RADS 4A were found significantly different in the malignant group compared to benign BI RADS 4A group. In total BIRADS 4 lesions, the ratio of PLT and RPR was significant in malignant group (p=0.047, p=0.002) in Complete Blood Count parameters compared benign and malignant group. Conclusion: Studies have shown that cancer affects peripheral blood cells positively or negatively. In our study, among peripheral blood cells, platelets were found to be the most affected in cancer patients. The PLT, PLR and RPR values could be valuable in predicting malignant BIRADS 4 breast lesions.
Keywords: Breast lesions; platelet; platelet to lymphocyte ratio